Kazakhstan energy policy: transition to renewable energy sources and development prospects (Journal of Philosophy Culture and Political Science, 2025)
The article analyzes the status, potential, and development prospects of renewable energy sources (RES) in Kazakhstan in the context of the global transition to carbon neutrality. Kazakhstan, traditionally focused on the use of hydrocarbons, is faced with the challenge of diversifying its energy balance and reducing carbon dioxide emissions. The article examines in detail the main types of RES available in the country, including solar, wind, hydro, and bioenergy. It analyzes how the natural and climatic conditions of Kazakhstan contribute to the development of these areas: the wind resources of the northern and central regions, the abundance of solar radiation in the south, and significant biomass reserves open broad opportunities for generating clean energy. Particular attention is paid to state policy and legislative measures to support RES, including the transition to an auction system for capacity distribution, introduced in 2018. This system has increased transparency, competitiveness, and attracted international investment. The article notes the important role of international cooperation: such organizations as the European Bank for Reconstruction and Development (EBRD), the United Nations Development Programme (UNDP) and the United States Agency for International Development (USAID) actively support Kazakhstan's initiatives to develop renewable energy sources, providing both technical and financial assistance. At the same time, the article highlights the existing barriers to the development of the renewable energy sector. These include high costs of equipment and infrastructure, difficult logistical conditions, extreme climatic factors and the need to adapt technologies. These obstacles must be addressed to achieve the goals set by the government, including to meet international commitments to reduce the carbon footprint.Keywords: renewable energy, energy potential, solar energy, wind energy, hydropower, bioenergy, carbon neutrality, auction system, green economy, international cooperation